2013
DOI: 10.1016/j.theriogenology.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive tract development and puberty in two lines of Nellore heifers selected for postweaning weight

Abstract: The objective was to evaluate reproductive tract development (ovary and uterus) and onset of puberty in two lines of Nellore heifers (Bos indicus) selected for postweaning weight. A total of 123 heifers, including 46 from the control Nellore line (NeC) and 77 from the selection Nellore line (NeS) were used. Every 18 to 21 days from 12 to 24 months of age, average ovarian area (OVA), endometrial thickness (ETh), and diameter of the largest follicle in each ovary were evaluated (using transrectal ultrasonography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
2
18
0
8
Order By: Relevance
“…Recently, Alves et al (2015) described that the reduction in neuropeptide-Y innervation of gonadotropin-releasing hormone neurons occurs in response to elevated body weight gain during the juvenile period. Nelore crossbred heifers had a higher heterozygosity, possibly due to a better adaptation to reach earlier puberty as described by Monteiro et al (2013). Interestingly, it was also observed that heifers fed a high concentrate diet showed a continuously high rate of body weight gain after weaning (Cardoso et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Recently, Alves et al (2015) described that the reduction in neuropeptide-Y innervation of gonadotropin-releasing hormone neurons occurs in response to elevated body weight gain during the juvenile period. Nelore crossbred heifers had a higher heterozygosity, possibly due to a better adaptation to reach earlier puberty as described by Monteiro et al (2013). Interestingly, it was also observed that heifers fed a high concentrate diet showed a continuously high rate of body weight gain after weaning (Cardoso et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Mercadante et al [42] estimated significant genetic trends of 1.78 ± 0.20 and 2.39 ± 0.20 kg/year for FW and non-significant genetic trends of 0.03 ± 0.16 and 0.19 ± 0.17 days/year for days to calving of the first mating in two lines that were selected for increased FW, respectively. Later, Monteiro et al [46] showed that selection for increased FW had no effect either on the development of the ovaries and the endometrium or the onset of puberty at 24 months of age in heifers. The selection for increased growth in performance-tested young bulls in feedlots will not change AFC in commercial heifers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the findings of our study may suggest a higher probability of the first pp ovulation occurring from the ROV than the LOV. Particularly, since mean ovarian size and endometrial thickness is reported to have a positive effect on reproductive activity [19]. The findings of this study may also imply that the frequency of pregnancy in the Lh is higher than in the Rh in SB goats because the ovary ipsilateral to the non-pregnant horn tends to resume activity earlier [20].…”
Section: Discussionmentioning
confidence: 58%